Can ordinary morality survive the climate crisis?: A philosophical analysis of moral demandingness and climate change - Puumala, Mikko M. (fi=Turun yliopisto|en=University of Turku|, 2023)
In this dissertation I examine how ordinary morality operates in the context of climate change, with a specific focus on moral demandingness. I will employ climate change as a conceptual stress test, to analyse how ordinary morality and its core principles can respond to climate change and the sacrifices required to mitigate it. The stress test reveals a conflict within the system of ordinary morality. On the one hand, ordinary morality’s key regulative principle, called over-demandingness principle, requires that agents must not be required to perform overly demanding acts. On the other hand, ordinary morality’s key moral principle, the no harm principle, requires that one must not cause unnecessary harm to others. But almost anything people do contributes to climate change, and thus causes harm to others. Not contributing to climate change would be extremely demanding. Thus, the two core principles are in conflict. I argue that ordinary morality can survive the climate stress test only by allowing more extreme demands, and I will show that this can be done without changing any of the core principles of ordinary morality. They require mere re-adjustments, although with the trade-off of accepting more extreme demands. This dissertation consists of three interlinked and mutually supportive threads: an argumentative thread, a methodological thread, and an explorative thread. The argumentative thread builds an institutional argument from the adaptive limits of human morality, which claims that because of human moral psychological limitations mitigating climate change ought to rely on institutional approaches. This argumentative thread also forms the operational space for ordinary morality and the stress test: the moral demands that follow from the imperative to mitigate climate change are related to demandingness of complying with institutional approaches, and this compliance implies great sacrifices for the individuals. The methodological thread applies the method of wide reflective equilibrium to ordinary morality. The method is utilised to identify and analyse the background theories, principles, and considered judgments that constitute ordinary morality. The reflective equilibrium process will conclude in a new point of equilibrium where ordinary morality can accommodate more extreme demands and survive the climate stress test. The explorative thread examines the morally demanding conditions of modern world. I suggest that the world is ‘morally far gone’, that is, it has reached a state where following even the moral obligations that adhere to ordinary morality is extremely demanding. I argue that this moral far-goneness is not a reason to reject ordinary morality. While we may desire a morally ‘clean slate’, that is, a situation where most of our everyday activities are morally permissible and do not contribute to harming others, this clean slate morality should not be the end-goal of moral theorizing, rather, it should be the end-goal of moral action guided my moral theories.

--- Tässä väitöskirjassa tutkin arkimoraalin toimivuutta ilmastonmuutoksen kontekstissa, kiinnittäen erityisesti huomiota moraalin vaativuuteen. Käytän ilmastonmuutosta käsitteellisenä stressitestinä analysoidakseni arkimoraalin ja sen keskeisten periaatteiden kykyä vastata ilmastonmuutokseen ja sen torjumisen vaatimiin uhrauksiin. Tämä stressitesti paljastaa ristiriidan arkimoraalin muodostavassa uskomusjärjestelmässä. Arkimoraalin keskeinen säätelevä periaate, niin sanottu ylivaativuusperiaate, edellyttää ettei toimijoilta vaadita ylivaativia tekoja. Toisaalta arkimoraalille keskeinen moraaliperiaate, haittaperiaate, edellyttää ettei muille saa aiheuttaa tarpeettomasti haittaa. Mutta lähes mikä tahansa mitä teemme kontribuoi ilmastonmuutokseen ja siten aiheuttaa haittaa muille. Olisi äärimmäisen vaativaa olla kontribuoimatta ilmastonmuutokseen jollain tavalla. Näin ollen, nämä kaksi keskeistä periaatetta ovat keskenään ristiriidassa. Argumentoin, että arkimoraali voi selvitä ilmastonmuutoksen aiheuttamasta stressitestistä vain hyväksymällä myös äärimmäisiä vaatimuksia, ja näytän, kuinka tämä on mahdollista muuttamatta yhtäkään arkimoraalin keskeisistä periaatteista. Näitä keskeisiä periaatteita on vain hieman säädettävä, vaikkakin sillä kustannuksella, että on myös hyväksyttävä äärimmäisempiä vaatimuksia. Tämä väitöskirja muodostuu kolmesta toisiinsa linkittyneestä ja toisiaan tukevasta punaisesta langasta, tai ajatusketjusta: argumentatiivisesta, metodologisesta ja eksploratiivisesta. Argumentatiivisessa ajatusketjussa muodostetaan institutionaalisen argumentin ihmisen moraalin adaptiivisista rajoista, joka väittää, että ihmisen moraalipsykologisten rajoitusten takia ilmastonmuutoksen torjumiseksi on käytettävä ensisijaisesti institutionaalisia ratkaisuja. Tämä argumentatiivinen ajatusketju muodostaa myös arkimoraalin ja stressitestin keskeisen toimintatilan: moraaliset vaatimukset, jotka seuraavat velvoitteestamme torjua ilmastonmuutos, liittyvät ensisijaisesti institutionaalisiin ratkaisuihin suostumiseen, ja niihin suostumiseen liittyy merkittäviä uhrauksia. Metodologinen ajatusketju soveltaa laajaa harkinnan tasapainomenetelmää arkimoraaliin. Kyseistä menetelmää käytetään tunnistamaan ja analysoimaan arkimoraalin muodostavia taustateorioita, periaatteita, ja harkittuja arvostelmia. Harkinnan tasapainomenetelmäprosessi johtaa uuteen harkinnan tasapainopisteeseen, jossa arkimoraali kykenee sisällyttämään itseensä myös äärimmäisempiä vaatimuksia, ja siten arkimoraali selviytyy stressitestistä. Eksploratiivinen ajatusketju tarkastelee nykymaailman moraalisesti vaativia olosuhteita. Ehdotan, että maailma on kaukana moraalisesti hyväksyttävästä, eli se on päätynyt tilaan, jossa jopa arkimoraalisten velvoitteiden noudattaminen on äärimmäisen vaativaa. Argumentoin, että tämä kaukana moraalisesti hyväksyttävästä tilasta oleminen ei anna perusteita hylätä arkimoraalia. Vaikka haluaisimme aloittaa moraalisesti “puhtaalta pöydältä”, eli tilanteesta, jossa suurin osa arkisista teoistamme on moraalisesti sallittuja eivätkä aiheuta haittaa muille, tällaisen puhtaan pöydän moraalin ei tulisi olla moraalisen teoretisoinnin päämäärä, vaan päinvastoin, meidän tulisi moraalisesti toimimalla pyrkiä moraalisten teorioiden avulla kohti moraalisesti puhdasta pöytää.